Reduction of Clostridium difficile Infection in a Community Teaching Hospital Associated with Antimicrobial Stewardship Team Interventions on Fluoroquinolone Utilization. (4th October 2017) - Politis, Paula; Abell, Virginia; Hoisington, Lisa; Tan, Michael J; File, Thomas M
Abstract: Background: In April 2016, the Antimicrobial Stewardship Program (ASP) at Summa Health System – Akron Campus (SHS-AC) began reviewing all fluoroquinolone use in addition to other daily responsibilities. The decision to do so was made following the formation of a Clostridium difficile reduction taskforce, comprised of Infection Control, Environmental Services, and the ASP. The primary goal of the taskforce was to reduce cases of hospital acquired C.difficile infections by 10%. The ASP collectively decided to focus on fluoroquinolone antimicrobials during the first year of implementation. Methods: A retrospective review of all ASP interventions at SHS-AC was performed from April 2016-April 2017. The ASP reviewed all patients on a fluoroquinolone without Infectious Diseases consultation. The appropriateness of the the dose and assessment of EKGs (if available) was performed on all patients. Patients were reviewed for the following information: indication, renal function, contraindications (e.g., QTc prolongation), drug-drug interactions (e.g., warfarin), and allergy status. Data collected included: infection source, intervention type, acceptance rate, hospital acquired C.difficile rate, and fluoroquinolone utilization. Results: A total of 612 recommendations were made by the ASP on fluoroquinolone use, with a 95% acceptance rate. Interventions included: change to alternative agent based on indication or culture results (302/612), stop or change antimicrobials due to contraindication or major drug interaction (86/612), and discontinue antimicrobial use (224/612). Ciprofloxacin utilization decreased from 15.8 days of therapy (DOT)/1000 patient-days in 2015, to 9.7 DOT/1000 patient-days in 2016. Levofloxacin utilization decreased from 11.2 DOT/1000 patient-days to 5.2 DOT/1000 patient-days in 2016. The healthcare associated C.difficile infection rate also decreased from 7.24/10, 000 patient-days in 2015, to 4.78/10, 000 patient-days in 2016. Conclusion: Fluoroquinolone evaluation and intervention performed by the ASP resulted in a reduction of fluoroquinolone utilization and likely contributed to the reduction of healthcare associated C.difficile rates. Disclosures: All authors: No reported disclosures.